2018
DOI: 10.1111/jam.14115
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis ofChloroflexipopulations in full-scale UASB methanogenic reactors

Abstract: Aims:The phylum Chloroflexi is frequently found in high abundance in methanogenic reactors, but their role is still unclear as most of them remain uncultured and understudied. Hence, a detailed analysis was performed in samples from five up-flow anaerobic sludge blanket (UASB) full-scale reactors fed different industrial wastewaters. Methods and Results: Quantitative PCR show that the phylum Chloroflexi was abundant in all UASB methanogenic reactors, with higher abundance in the reactors operated for a long pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…At phylum level, the proportion of Chloroflexi was the highest no matter in which compartment, and it was in good accordance with some pervious reports. It has been widely reported that Chloroflexi is abundant in anaerobic digestion reactors, and the potential capacity of Chloroflexi for carbohydrate degradation was reported in previous studies (Bovio et al, 2019;Rivière et al, 2009). Firmicutes was also pointed out as being related to the degradation of carbon compounds.…”
Section: Discussionmentioning
confidence: 90%
“…At phylum level, the proportion of Chloroflexi was the highest no matter in which compartment, and it was in good accordance with some pervious reports. It has been widely reported that Chloroflexi is abundant in anaerobic digestion reactors, and the potential capacity of Chloroflexi for carbohydrate degradation was reported in previous studies (Bovio et al, 2019;Rivière et al, 2009). Firmicutes was also pointed out as being related to the degradation of carbon compounds.…”
Section: Discussionmentioning
confidence: 90%
“…The phylum ‘ Chloroflexi , embraces an ecologically and physiologically diverse group of bacteria, which have been detected in an increasingly wide range of anaerobic habitats including sediments, hot springs, methanogenic anaerobic sludge digesters where they are highly abundant and play an important fermentative role as well as contributing to sludge granulation (Hug et al, 2013; McIlroy et al, 2016; Sun et al, 2016; Xia et al, 2016; Petriglieri et al, 2018; Bovio et al, 2019), the human oral cavity (Campbell et al, 2014), Anammox reactors (Kindaichi et al, 2012; Cao et al, 2016; Wang et al, 2016) and activated sludge communities (Björnsson et al, 2002; Kragelund et al, 2007a, 2011; Speirs et al, 2009, 2011, 2017; Yamada and Sekiguchi, 2009; Hanada, 2014; McIlroy et al, 2018; Andersen et al, 2019; Nierychlo et al, 2019). This is not the place to explore in detail their still evolving systematics, which have been dealt with elsewhere (Hanada, 2014).…”
Section: The Chlorofleximentioning
confidence: 99%
“…Despite the Chloroflexi bacteria being among the first widespread microbial lineages discovered in deep-sea environments we still lack cultured representatives (especially those with relative fast growing rate) for this group and their detailed physiological, genetic and ecological properties are currently almost completely obscure [13,23,24]. For example, until now, only basic physiological characteristics of two cultured strains of Chloroflexi with extremely slow growth rate (doubling time from 1.5 days to 19 days) from the deep-sea sediments are available [10,23], and their central metabolisms and contributions to biogeochemical processes including sulfur cycling are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms are the primary drivers of elemental cycles within deep marine subsurface sediments and play key roles in the recycling of biogeochemical nutrients to the water column [4]. Members of the phylum Chloroflexi widely distributed in various environments with high abundance, for example, in some marine subsurface sediments the number of Chloroflexi bacteria is shown to be closely equivalent to other total bacterial counts [3,[5][6][7][8], strongly suggesting that the phylum Chloroflexi is an essential group to maintain the population equilibrium of marine subsurface ecosystems [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%